PENGARUH EARNINGS MANAGEMENT TERHADAP FIRM VALUE - Susanto, Sherly (Business Accounting Review, 2016)
The affect of earnings management to firm value had been studied before. However, the previous studies showed the inconsistent results. The aim of this research was to examine the affect of earnings management toward firm value in manufacturing sector in Indonesia by using various control variables such as firm size and leverage.The data in this study were processed by using SPSS version 22. The samples used in this study were 124 observations in the manufacturing sector that were listed in Indonesian Stock Exchange in the period of 2010-2014. The study found that earning management and firm size had positive significant affect to firm value. Besides, the study also found that leverage had a negative significant affect to firm value.